The Tutorial Environmental Integration in Development Strategy and Economic Growth: A Macroeconomic Perspective - Sungkawaningrum, Fatmawati (Teumulong: Journal of Community Service, 2024)
This researchoutlines how macroeconomic policies and actions can contribute to environmental sustainability while achieving stable economic growth. The problem is that uncontrolled economic growth and lack of attention to the environment have resulted in significant negative impacts, such as climate change and ecosystem degradation.The aim of this research is to explore the integration of environmental factors in development strategies and economic growth. This research method involves literature analysis, environmental impact assessment, and tracking sustainable macroeconomic policies. The research results show that environmental integration in macroeconomics is the key to achieving sustainable economic growth. This involves the use of strict environmental regulations, development of sustainable economic sectors, investment in technological innovation, and cooperation with the private sector. In conclusion, the integration of the environment in development strategies and economic growth brings economic and environmental benefits. In facing ongoing macroeconomic challenges, balanced policies between economic and environmental interests are needed to achieve sustainable development goals.